2015
DOI: 10.1002/tesq.258
|View full text |Cite
|
Sign up to set email alerts
|

Metacognition in L2 Listening: Clarifying Instructional Theory and Practice

Abstract: W ithin the framework of metacognition in second language (L2) listening, there has been a notable surge in the amount of research being conducted and published regarding the effects of metacognitive instruction. Nevertheless, despite this positive interest, it is becoming increasingly evident that there is an element of misunderstanding among researchers, reviewers, and scholars about what constitutes metacognitive instruction. Moreover, there is apparent confusion in a number of associated publications regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 30 publications
1
11
0
2
Order By: Relevance
“…After the intervention, the learner developed not only her metacognitive knowledge but also listening comprehension. It is important to note that metacognitive instruction differs from strategy instruction in that strategy instruction involves explicit teaching of strategies (e.g., how to use a dictionary) that are not necessarily designed to impact learners’ cognitive processing (see Cross, ).…”
Section: Background Literaturementioning
confidence: 99%
“…After the intervention, the learner developed not only her metacognitive knowledge but also listening comprehension. It is important to note that metacognitive instruction differs from strategy instruction in that strategy instruction involves explicit teaching of strategies (e.g., how to use a dictionary) that are not necessarily designed to impact learners’ cognitive processing (see Cross, ).…”
Section: Background Literaturementioning
confidence: 99%
“…Additionally, metacognition lies as the heart of learneroriented L2 listening comprehension because it is fundamental to help learners involve more effectively with contribution and lead their overall listening development like language input they receive, manage their approach to listening, focus on the spoken message, and boost their performance on listening activity in and out of the classroom (Rahimirad & Shams, 2014). Research on metacognition in second language (L2) listening becomes positive interest among researchers, reviewers, and scholars (Cross, 2015) and some studies on learners' metacognition have exposed the important role of metacognitive knowledge in L2 listening performance (Vandergrift, et al, 2006;Goh & Hu, 2013;Bozorgian, 2014;Rahimi & Abedi, 2015;Vandergrift & Baker, 2015). Goh and Hu (2013) found that learners' metacognitive knowledge scores, their listening performance, and metacognitive awareness in listening were significantly correlated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent years have seen increased attention on metacognitive instruction in second/foreign language listening research. Metacognitive instruction was vaguely defined in second language (L2) listening research and entangled with the strategy instruction (Cross, 2015). Cross (2015) unravelled the differences by pinpointing that metacognitive instruction aimed to develop the metacognitive knowledge and listening strategies, as opposed to the strategy instruction that mainly emphasized developing strategy use.…”
Section: Introductionmentioning
confidence: 99%
“…Metacognitive instruction was vaguely defined in second language (L2) listening research and entangled with the strategy instruction (Cross, 2015). Cross (2015) unravelled the differences by pinpointing that metacognitive instruction aimed to develop the metacognitive knowledge and listening strategies, as opposed to the strategy instruction that mainly emphasized developing strategy use. Thus, designing metacognitive instruction should involve reflective activities that could elicit learners' thinking on their metacognitive knowledge (Goh, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation